Outcomes of manual small incision cataract surgery under topical anesthesia with lignocaine 2% jelly - Mithal, C; Agarwal, P; Mithal, N (Nepalese Journal of Ophthalmology, 2012)
Introduction: The manual small incision cataract surgery (MSICS) is the surgery of choice in countries with a huge back-log of cataract blindness. Objective: To evaluate the outcome of manual small incision cataract surgery (MSICS) under topical anesthesia with lignocaine 2 % jelly. Materials and methods: This study was a prospective interventional case series. One hundred and twenty eight patients of senile cataract were operated by MSICS under topical anesthesia using lignocaine 2% jelly. No intra-cameral anesthesia was used. The patients and the single operating surgeon were given a questionnaire to evaluate their experience in terms of pain, surgical experience and complications. Results: The mean pain score was 0.82 (SD ± 0.97). Seventy-one patients (55.4 %) had a pain score of zero, that is, no pain. One hundred and twenty one patients (94.5 %) had a score of 3 or less, that is, mild to none pain. All the surgeries except two were complicationfree and the surgeon’s experience was favorable in terms of the patient’s cooperation, anterior chamber stability, difficulty, and complications. Conclusions: MSICS can be performed under topical anesthesia with lignocaine jelly, which makes the surgery patient-friendly, without compromising the outcome. DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5862 NEPJOPH 2012; 4(1): 114-118